Determinants of Actuarial Cost Method Changes for Pension Accounting and Funding - Ghicas, Dimitrios C. (The Accounting Review, 1990)
[The choice of the appropriate actuarial cost method was an important issue considered at the different stages of the process that led to the promulgation of the SFAS No. 87, "Employers' Accounting for Pensions." Actuarial cost methods have been used by firms for accruing periodic pension expenses and determining the funding of defined-benefit pension plans. These methods have been classified by actuaries into cost-allocation methods and benefit-allocation methods. This study identifies and evaluates some possible determinants of the switch from a cost-allocation actuarial cost method to a benefit-allocation actuarial cost method. The primary effects of this switch are a decrease in pension expense and in the amount funded to the pension plan. The decreases in pension expense and funding arise because benefit-allocation methods have lower pension liabilities than do cost-allocation methods. This study hypothesizes that the primary reasons for the switch in actuarial cost methods are: a reduction in contracting costs, a decline in the taxpaying status and the earnings performance, and a preference for internal over external sources of funds for financing investment outlays. In addition, the study examines whether an actuarial alignment of pension assets to the reported present value of the accumulated plan benefits motivates the switch in actuarial cost methods and controls for the effect of differing interest rates in the computation of the accumulated plan benefits. The hypotheses are tested by comparing switch firms to industry-matched nonswitch firms and using proxy measures to operationalize the theoretical concepts. The comparisons are performed in the year prior to the switch, the year of the switch, and the year following the switch by relying on multivariate logit models. The primary advantage of logit models is the presence of consistent coefficient estimates whenever choice-based sampling is involved. Univariate matched-pairs t-tests and Wilcoxon sign-rank tests are also performed in the year of the switch. The empirical findings suggest that financial statement considerations and reduction in pension funding appear to be the primary reasons associated with the switch in actuarial cost methods. The reduction in pension funding is first accomplished by the use of higher interest rates, which decrease pension liabilities, and then by the switch into a benefit-allocation method, which provides an additional decrease in the pension liabilities. The last step is used if firms have limited freedom to make further increases in interest rates as unreasonably high interest rates are not permissible under ERISA. Empirical evidence based on multivariate logit models reveals a lower current assets to current liabilities ratio, a slower rate of investing into new projects, and a higher long-term debt to total tangible assets ratio for switch firms in comparison to their nonswitch counterparts for the year of the switch. To the extent that these relationships reflect a higher probability of technical default for switch firms, the findings are consistent with both the pension funding literature (Francis and Reiter 1987) and the accounting method choice literature (Holthausen and Leftwich 1983). In addition, this study points out the importance of an interactive effect between working capital ratio and rate of undertaking new investments in that increasing levels of working capital are needed to sustain higher rates of new investments.]